İstanbul’da okul çağındaki çocukların beslenme davranışı, ağız sağlığı ile tükürükte porphyromonas gingivalis ve bifidobacterium türleri varlığının araştırılması - OMURTAG KORKMAZ, BURCU İREM; İSLAMOĞLU, AYŞE HÜMEYRA (My University, 2022)
Objective: One of the most important environmental factors affecting oral-dental health is nutrition. This study aimed to investigate the relation of Body Mass Index (BMI) and dietary habits to the oral-dental health of children, and the presence of Porphyromonas gingivalis and Bifidobacterium species in saliva. Methods: One-hundred-thirty children between the ages of 9-14 were included in the study. Decayed, Missing, and Filled Teeth/Surfaces (DMFT, DMFS) of permanent, and decayed and filled teeth/surfaces (dft, dfs) of primary teeth were recorded, and plaque (PI) and gingival (GI) indexes were also assessed. Anthropometric measurements and food records were taken, and saliva samples were analyzed microbiologically. Results: A negative correlation between BMI and dft, dfs scores, and a positive correlation between BMI and oral-dental health parameters was found (p<0.05). A positive correlation was also found between the visiting frequency of children to dentists and GI. Mutual interactions between PI and GI, DMFT and DMFS, a strong interaction between dft and dfs indexes was observed. Saliva Bifidobacterium sp. was significantly related to dft, dfs indexes. BMI, Bifidobacterium sp., DMFT, DMFS scores increased with age. None of the children had P.gingivalis in saliva, while 3.1% had Bifidobacterium sp.. A positive correlation occurred with bread consumption, whereas a negative correlation occurred in grain consumption with a comparison of the DMFS index (p<0.05). Sugar intake was positively correlated; total dietary fiber intake was negatively correlated with PI (p<0.05)

Objective: One of the most important environmental factors affecting oral-dental health is nutrition. This study aimed to investigate the relation of Body Mass Index (BMI) and dietary habits to the oral-dental health of children, and the presence of Porphyromonas gingivalis and Bifidobacterium species in saliva. Methods: One-hundred-thirty children between the ages of 9-14 were included in the study. Decayed, Missing, and Filled Teeth/Surfaces (DMFT, DMFS) of permanent, and decayed and filled teeth/surfaces (dft, dfs) of primary teeth were recorded, and plaque (PI) and gingival (GI) indexes were also assessed. Anthropometric measurements and food records were taken, and saliva samples were analyzed microbiologically. Results: A negative correlation between BMI and dft, dfs scores, and a positive correlation between BMI and oral-dental health parameters was found (p<0.05). A positive correlation was also found between the visiting frequency of children to dentists and GI. Mutual interactions between PI and GI, DMFT and DMFS, a strong interaction between dft and dfs indexes was observed. Saliva Bifidobacterium sp. was significantly related to dft, dfs indexes. BMI, Bifidobacterium sp., DMFT, DMFS scores increased with age. None of the children had P.gingivalis in saliva, while 3.1% had Bifidobacterium sp.. A positive correlation occurred with bread consumption, whereas a negative correlation occurred in grain consumption with a comparison of the DMFS index (p<0.05). Sugar intake was positively correlated; total dietary fiber intake was negatively correlated with PI (p<0.05)
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Nutrition; Dental health; Porphyromonas gingivalis; Bifidobacterium; Beslenme; Diş sağlığı